2020
DOI: 10.18632/oncotarget.27559
|View full text |Cite
|
Sign up to set email alerts
|

Changes in microRNA expression associated with metastasis and survival in patients with uveal melanoma

Abstract: Uveal melanoma (UM) is a major intraocular cancer that is molecularly distinct from cutaneous melanoma. Approximately half of patients with UM eventually develop metastasis. The prognosis of metastatic UM is poor, with a median overall survival (OS) of less than a year. In this study, we sought to identify microRNAs (miRNAs) associated with metastasis and OS in UM. We analyzed the miRNA expression and clinical outcomes data from The Cancer Genome Atlas (TCGA) dataset for UM. Differential expression analyses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…Similarly, Gasparello et al (39) found that hsa-miR-221-3p did not discriminate between early CRC patients and healthy donors. In agreement with our findings, Deng et al found that high hsa-miR-221-3p expression was associated with better 5-year disease-free survival of triplenegative breast cancer patients (40), and in uveal melanoma, Vashishtha et al (41) found that the downregulation of hsa-miR-221-3p was associated with metastatic disease. Some reports on melanoma and hsa-miR-221 did not specify whether−5p or−3p species were analyzed (37).…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, Gasparello et al (39) found that hsa-miR-221-3p did not discriminate between early CRC patients and healthy donors. In agreement with our findings, Deng et al found that high hsa-miR-221-3p expression was associated with better 5-year disease-free survival of triplenegative breast cancer patients (40), and in uveal melanoma, Vashishtha et al (41) found that the downregulation of hsa-miR-221-3p was associated with metastatic disease. Some reports on melanoma and hsa-miR-221 did not specify whether−5p or−3p species were analyzed (37).…”
Section: Discussionsupporting
confidence: 93%
“…Hsa-miR-513a-5p, miR-506-3p, miR-508-3p, miR-140-3p, and miR-103a-2-5p were further identified as OS signatures via Cox LASSO regression, and the results were confirmed by the KM plot and ROC curve. Other bioinformatics methods were also applied to explore microRNAs related to the invasion [ 33 ] and prognosis [ 34 , 35 ] of UM based on a TCGA dataset. However, most of the microRNAs we identified except hsa-miR-513a-5p differed from those identified in other studies due to the various methods used.…”
Section: Discussionmentioning
confidence: 99%
“…The association of miRNA expression, metastasis, and survival in patients with UM using the TCGA dataset was also investigated by Vashishtha et al [ 98 ]. They reported 22 miRNAs, 3 upregulated (miR-199a-5p, miR-708-5p, and miR-592), and 9 downregulated (miR-508-3p, miR-509-3p, miR-508-5p, miR-514a-3p, miR-506-3p, miR-509-3-5p, miR-513c-5p, miR-513a-5p, and miR-513b-5p) in patients with vs. those without metastatic UM.…”
Section: Mirna and Uveal Melanomamentioning
confidence: 99%